PENGEMBANGAN MEDIA TIGA DIMENSI UNTUK MENINGKATKAN LIFE SKILLS MAHASISWA PENDIDIKAN SEJARAH IKIP PGRI MADIUN - Hanif, Muhammad (Jurnal Pendidikan, 2008)
One out of some objectivesÂ  of carryingÂ  out the scholarshipÂ  of the History StudyÂ  ProgramÂ  of IKIPÂ Â  PGRI MadiunÂ  is to enhance:Â  (1) teachersÂ  who have sufficientÂ  competenceÂ Â  in their teachingÂ  skill, (2) teachersÂ  who are sensitiveÂ  towardsÂ  the progressÂ  of the history and all social process within the society, 3) teachersÂ  who are flexibleÂ  against the developmentÂ Â  of historyÂ  of IndonesiaÂ Â Â  byÂ  havingÂ  the historical awarenessÂ  as front-linersÂ  of educationalÂ Â  conducts.Â  The competence copesÂ  with competenceÂ Â  and qualificationÂ Â  at the cognitive,Â  affective and psychomotorÂ  domains.Â  Such a competenceÂ Â  leads the learnersÂ  to life-skillÂ Â Â  thatÂ Â  studentsÂ  shouldÂ Â  copeÂ Â  with.Â  AmongÂ Â  someÂ Â  ways developingÂ  the lecturers competenceÂ  at the three domainsÂ  mentioned aboveÂ  in generatingÂ Â  the, studentsÂ Â  life-skill,Â Â  itÂ  isÂ  suggestibleÂ Â  that lecturers developÂ  teachingÂ  method. Three-dimensionÂ Â  teachingÂ  media is oneÂ  methodÂ  thatÂ  is presumptivelyÂ Â  ableÂ  to developÂ  the lecturersÂ competenceÂ  in generatingÂ  the studentsÂ  life-skill. This research serves an analysis on the significanceÂ  of the use of three-dimensionÂ  teaching mediaÂ  onÂ  theÂ  studentsâ life skill.Â  ThisÂ  research,Â Â  then,Â  proposes objectivesÂ  as to identify the significanceÂ  of three-dimensionÂ Â  teaching media towardsÂ  the studentsÂ  life-skill.The researchÂ  methodÂ  appliedÂ  in this researchÂ  is ResearchÂ  and DevelopmentÂ  coping with three stages, i.e.: (1) explorationÂ  under qualitativeÂ  descriptiveÂ  method, (2) developmentÂ  under single one shot case study, (3) experimentationÂ Â  method. The subjects of the study are all of the students of the History Study Program of IKIP PGRI Madiun.The research lasts in drawing conclusionÂ  that the development of three-dimensionÂ Â  teachingÂ  media can analyticallyÂ  improve life skill of the students of History Study Program of IKIP PGRI Madiun. Then the hypothetic model as shown in figure 1 is attested already as it is shown in figure 2 and 3 under attested consistence and validity in generating the life-skill of the students of History Program of IKIP PGRI Madiun.Key terms: three-dimension teaching media, life-skill